Podoba mesta Sao Paolo - prepoznavnost in kriza - Rocco, Roberto (Urbani izziv, 2003)
Although Brazil is renown worldwide for its fascinating 20. century modernist architecture, the ongoing contemporary architecture is increasingly moving away from former avant-garde and cosmopolitan ideals as well as physical form.In Sao Paulo, the country's largest city, high quality and typical architectural design has been crumbling before the onslaught of poorly articulated consumer demands and the property market for decades. The phenomenon of the neoclassical style is causing increasing revolt from representatives of the urban elite, the reasons being loss of aesthetic values, no knowledge of identity and hurt national pride.
Keywords: architecture; arhitektura; Brazilija; modernizem; neoklasicizem; Sao Paolo; urbanism; urbanizem